DAMPAK KONSUMSI MAKANAN CEPAT SAJI TERHADAP KESEHATAN METABOLIK MAHASISWA DI ERA FOOD DELIVERY ONLINE - Hadi Nur Efendi; Ayik Nikmatul Laili; Mohammat Fairosi (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The advancement of digital technology has facilitated easier access to fast food through online food delivery services. This phenomenon influences students’ eating patterns, which tend to favor convenient but less healthy meals. This study aims to analyze the impact of fast food consumption on students’ metabolic health, including body weight, blood glucose levels, and lipid profiles. A quantitative survey method was employed using purposive sampling of 120 students from various faculties at University X. Data were collected through a fast food consumption frequency questionnaire, interviews, and simple health examinations. The results indicate that high fast food consumption frequency is associated with increased body weight, elevated cholesterol, and above-normal blood glucose levels. In conclusion, excessive fast food consumption in the era of online food delivery has the potential to trigger metabolic disorders among students.